Expatriates Adjustment And Job Performance: An Examination Of Individual And Organizational Factors - Muhammad Awais Bhatti,; Mohamed Mohamed Battour,; Ahmed Rageh Ismail (Emerald Group Publishing Limited, 2024)
Indexed by Scopus